FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN SELF-EFFICACY PERAWAT DALAM MELAKUKAN RESUSITASI JANTUNG PARU PADA MASA COVID-19 - Annisa Hilmy Nurarifah, (2021)
Cardiac arrest is a loss of heart function that can occur suddenly both outside and within the hospital area. Handling in cardiac arrest is the provision of cardiopulmonary resuscitation carried out by medical personnel at the hospital, one of which is a nurse. The quality of giving cardiopulmonary resuscitation can be influenced by the nurse's self-efficacy so that having good self-efficacy can improve the results of cardiopulmonary resuscitation. There are factors that affect the current condition of COVID-19 which makes medical personnel have to improve their safety while providing services and treatment to patients in hospitals. This research is using approach Cross Sectional with (30) samples which is obtained with accidental sampling technique. This instrument research is a questionnaire that already tested the validity and reliability. This research get results that the related factors is Gender (p value = 0,01), Mastery Experiance (p value= 0,01), and Verbal Persuasion (p value =0,03). While the factor that not related is ages (p value=0,765), education (p value=0,73), length of work (p value=0,22), Family status (p value =0,81), CPR Trainning (p value =0,34), knowladge (p value=0,98), and the availability of personal protective equipment (p value=0,49).